Pengaruh Return On Equity (Roe), Investment Opportunity Set (Ios), Debt To Equity Ratio (Der), Dan Dividend Payout Ratio (Dpr) Terhadap Nilai Perusahaan pada Perusahaan Manufaktur di Bursa Efek Indonesia Periode 2014-2017 - Lidya Anggraeni (Journal Development, 2020)
This study aims to determine the effect of ROE, IOS, DER and DPR on the value of the company in the manufacturing industry listed on the Indonesia Stock Exchange (IDX) in 2014-2017, both partially and simultaneously. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2014-2017, the study sample of 13 manufacturing companies obtained by purposive sampling technique. The data collection technique used is documentation. Data analysis was performed by multiple regression analysis techniques. The results of the study show that simultaneously the ROE, IOE, DER and DPR variables together influence the firm value and partially only the IOS and DER variables that have a positive effect on the value of the company, ROE, and DPR negatively affect the value of the company.